(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
Studies reveal that the symptoms of those who have mood disorders exert effect on their families, by annoying their life and causing them to develop hostile attitudes toward the ill person. The objective of this work is to contribute to improve relationships among the family members. The results, obtained from the questionnaires and reports of the family members, showed that the majority had very vague or erroneous ideas aboutmooddisorders and knew little or nothing about the diagnosis received by the patient. All of them, in someway, were affected by the symptoms of the ill person. The psycho educational program contributed to improve the relationship with the patient, to provide more support and to promote well-being for the family members.